Prognostic Value and Clinical Impact of 18FDG-PET in the Management of Children with Burkitt Lymphoma after Induction Chemotherapy - Bailly, Clément; Eugène, Thomas; Couec, Marie-Laure; Strullu, Marion; Frampas, Eric; Campion, Loïc; Kraeber-Bodéré, Françoise; Bodet-Milin, Caroline (Frontiers in Medicine, 2014)
Objective: Burkitt Lymphoma (BL) is a rare and aggressive form of B cell lymphoma that is curable using intensive chemotherapy. Obtaining a complete response (CR) at the end of induction chemotherapy is a major prognostic factor. This study retrospectively evaluates the potential impact of 18FDG-PET in the management of children with BL after induction chemotherapy, and the prognostic performance of the Deauville criteria. Methods: 19 children with BL treated according to the French LMB2001 protocol between 2005 and 2012 were included. 18FDG-PET and conventional imaging (CI) were performed after induction chemotherapy to confirm CR. 18FDG-PET was interpreted according to Deauville criteria with follow up and/or histology as the gold standard. Results: 18FDG-PET was negative in 15 cases, in agreement with CI in 9/15 cases. The six discordant cases confirmed to be negative by histology, were considered as true negative for 18FDG-PET. Negative predictive value (NPV) of CI and 18FDG-PET were 73 and 93% respectively. The five-year PFS was significantly higher in patients with negative 18FDG-PET than those with positive 18FDG-PET (p=0.011). Conclusion: 18FDG-PET interpreted using Deauville criteria can help confirm CR at the end of induction chemotherapy, with a prognostic impact on five-year PFS. Its high NPV could limit the use of residual mass biopsy. Given the small size of our population, these results need to be confirmed by future prospective studies on a larger population.